How Did the COVID-19 Pandemic Affect Trends in Facial Trauma?. Issue 2 (June 2022) - Stanisce, Luke; Fisher, Alec H.; Choi, Bo Young; Newman, Andrew; Wang, Ju Lin; Koshkareva, Yekaterina
Study Design: Retrospective cohort analysis. Objective: To examine the impact the COVID-19 pandemic and its accompanying societal measures had on the incidence, characteristics, and management of maxillofacial traumatic injuries. Methods: This cohort analysis compared facial trauma injuries presenting to the highest-volume Level I Trauma Center in New Jersey, USA from January 1 to July 31 in 2020 and 2019. Differences in demographics, mechanisms, and interventions were compared between the pandemic period (March 16–July 31, 2020) and the equivalent pre-pandemic date period in 2019 using X 2, Fishers Exact, and Mann–Whitney U testing. Results: In total, 616 subjects were included. The daily incidence of facial trauma consults during the 2020 pandemic (1.81 ± 1.1) decreased compared to 2019 (2.15 ± 1.3) ( p = 0.042). During the outbreak, there was an increase in the proportion of subjects with positive urine drug screens (21.5% vs. 12.2%; p = 0.011) and injuries related to domestic violence (10.2% vs. 4.5%; p = 0.023). Patients were 30% less likely to be transferred from local hospitals (RR, 0.70 [0.53–0.93]; p = 0.014). Although subjects had a 25% increased risk of presenting with injuries deemed procedural (RR, 1.25 [95% CI, 1.05–1.56]; p = 0.048), a greater proportion were discharged with operative procedures scheduled as outpatients (16.0% vs. 4.9%; p = 0.005). Conclusions: The COVID-19 pandemic has impacted both the epidemiology and management of maxillofacial traumatic injuries, perhaps secondary to modifications in personal and community behaviors or the effects on healthcare systems in our region.